A recombinant BCG with surface-displayed antigen induces humoral and cellular immune responses - Jin-Yu Zhang; Zhi-Dong Hu; Li-Xiao Xing; Zhen-Yan Chen; Jin-Chuan Xu; Qiao-Yu Wu; Juan Wu; Guo-Ping Zhao; Xiao-Yong Fan; Liang-Dong Lyu (Scientific Reports)
Abstract Bacillus Calmette-Guérin (BCG) is an attenuated vaccine widely used for tuberculosis prevention. While BCG has long been perceived as an intracellular candidate vector for delivering antigens against infectious diseases and cancers, challenges persist in inducing durable immune responses, particularly high-titer neutralizing antibodies (Nabs). Here we show that displaying antigens in the surface of BCG is a promising strategy to induce long-lasting Nabs production and T-cell responses. We constructed a recombinant BCG expressing the SARS-CoV-2 receptor-binding domain (RBD) antigen on its cell wall, termed CW-rBCG::RBD, which achieved an antigen yield approaching 850 nanograms per 107 colony-forming unit. Compared with both the parental BCG and the RBD protein subunit vaccine (RBDAS01), intravenous administration of CW-rBCG::RBD followed by a booster dose significantly enhanced Nab production and increased the frequencies of RBD-specific central memory T cells (Tcm) and T follicular helper (Tfh) cells in the spleen. In mice primed with a single dose of CW-rBCG::RBD and boosted with RBDAS01, we also observed elevated Nab titers and detectable levels of RBD-specific IgG2a antibodies at 8 weeks post-priming, responses that were not observed in the BCG-primed or RBDAS01-only groups. Furthermore, subcutaneous co-administration of CW-rBCG::RBD and RBDAS01 sustained Nab production for up to 31 weeks and maintained higher Tfh and Tcm cell frequencies compared to both BCG co-administration with RBDAS01 and RBDAS01 alone. These findings highlight an effective strategy for optimizing BCG-based vaccination and immunotherapy platforms. Subject terms: recombinant BCG; immune response; vaccines; cell wall; SARS-CoV-2 RBD.